Recurrent Abdominal Pain in Children; Role of Psychological Intervention in Functional Abdominal Pain (Bangladesh Journal of Child Health, 2025)
Background: Abdominal pain is a common health problem of pediatric age group. The pain may have underlying disease or may be functional. Functional abdominal pain has major impact on children and their families and if untreated may persists into adult life. Psychotherapy can improve functional abdominal pain. This study evaluates the physical factors behind recurrent abdominal pain in children and role of cognitive behavioral therapy in functional pain disorder. Materials and methods: A total of 140 children of 4 to 15 years with recurrent pain in abdomen admitted in Dr M R Khan Shishu Hospital were enrolled in a case control study. Detailed history was taken following thorough physical examination. Complete blood count, urine and stool routine examination and ultrasonogram of whole abdomen were done in all cases. Further investigations were done upon clinical suspicion like stool OBT, SGPT, serum Amylase, Lipase, tissue transglutaminase, tuberculin test, plain X-ray abdomen, upper GI Endoscopy. When organic pathology was found, that was treated. Children fulfilling the ROME IV criteria for functional abdominal pain were considered to have non- organic (functional) pain. Children having functional pain were divided into 2 groups. Some children received cognitive behavioral therapy, were taken as case and those who did not willing to receive psychotherapy were taken as control. Both groups were followed up after 6 months and improvement was noted. Results: Among total 140 children, male were 58% and female 42%. Maximum children (44%) were between 8 to 11 years of age. Common organic causes of pain were constipation (37.35%), urinary tract infection (21.69%), peptic ulcer disease (15.66%), appendicitis (10.84%), cholecystitis (6%). Functional abdominal pain was found in 57(41%) cases. Among them 22 children received short term cognitive behavioral therapy and 18 did not. Children received cognitive behavioral therapy, improved significantly after 6 months in context of reduced pain frequency, improved appetite and good school performances than those who did not receive therapy. Conclusion: Constipation, urinary tract infection, peptic ulcer disease are common organic causes of abdominal pain. Functional abdominal pain is a predominant cause of recurrent abdominal pain that is significantly ameliorated by cognitive behavioral therapy.BANGLADESH J CHILD HEALTH 2023; VOL 47 (3) : 157-161